Gender Construction in Malaysian Children’s Literature - S. Raman Nair, Ramesh Nair (2008)
The present study explores the construction of gender in a selection of Malaysian children’s literature texts in the English language. An examination of the ways in which male and female social actors are constructed in these texts uncovers the subtle gender-based messages that they inherently contain. This is important to know because young Malaysian children reading these stories are also building sociocognitive schemas about their gender identity and roles in society. The content analytic method of liberal feminist researchers has been a popular method of evaluating the representation of male and female characters in children’s stories. Such research has served to reveal, among others, imbalances in the number of male and female characters found in lead roles and in illustrations. The present study adds another dimension to the reading of gender in children’s literature. In addition to looking at gender through a content analysis of surface level features, the way in which the various characters are linguistically and visually constructed is also examined. It is for these reasons that Critical Discourse Analysis (CDA) is adopted as an approach to reading gender construction in children’s literature. CDA is an approach that looks at how power imbalances are played out through choices made in language use and related semiotic resources. Four methods of analysis are relied upon and they are content analysis, lexical analysis, transitivity analysis and visual analysis. It is the researcher’s contention that each method contributes to a comprehensive framework for reading gender in children’s literature. The findings of the content analysis revealed significant imbalances in the distribution of female and male social actors, both in the roles that they played and their appearances in the accompanying illustrations. In both cases, males outnumbered females. Practices of stereotyping were found in the distribution of the characters in the various settings. While the home setting appeared established as a feminised space, the workplace and outdoor settings were dominated by males. The content analysis also pointed towards stereotyping practices in the way female and male characters were ascribed behavioural traits and status in society. The association between gender and behavioural trait appeared to firmly establish power in the hands of the male characters. In the next stage of analysis that focused on both written and visual language, strong nuances of sexism were identified in apparently neutral texts, revealing a weaker construction of females. The analysis of lexical units and clauses revealed deeply embedded linguistic structures that positioned males as predominantly more powerful than the female characters. The visual analysis focused on the roles the female and male characters took on in the illustrations and it was again found that male characters were accorded the more important roles of active doer while females took on the role of passive observer.An analysis of language, both written and visual, which is grounded in CDA, offers researchers and decision-makers in the selection of texts for children greater insights into the way gender is subtly constructed. As such, the present study proposes that language should be accorded greater attention in the evaluation of gender construction in children’s literature or in literary texts produced for children.